Blockchain Enabled Consumer Data Sovereignty for Privacy Oriented Digital Governance - Denok Wahyudi Setyo Rahayu; Muhamad Firdaus; Abdullah Arif Kamal (CORISINTA, 2026)
This study examines blockchain technology as an enabling infrastructure for consumer centric data governance through the conceptual lens of the sovereign consumer. Departing from platform centric models that frame data privacy primarily as a regulatory compliance or technical security issue, this paper positions consumer sovereignty as both a governance principle and an operational capability. Using a qualitative and analytical research design, the study synthesizes insights from consumer sovereignty theory, digital governance literature, and decentralized systems research to conceptualize how blockchain characteristics namely decentralization, immutability, transparency, cryptography, and smart contracts can be mapped onto core data governance functions. The analysis demonstrates that blockchain has the potential to transform data ownership from a passive legal status into an enforceable and programmable right, allowing individuals to dynamically grant, monitor, and revoke consent over personal data usage. Rather than relying on absolute data concealment, privacy is operationalized through controlled transparency supported by cryptographic safeguards and hybrid on chain and off chain architectures. This governance oriented framework emphasizes accountability, auditability, and user authority without compromising regulatory alignment. Although the proposed framework remains conceptual and does not involve empirical implementation, it provides a structured analytical contribution relevant to AI driven digital ecosystems and sustainable digital development. In particular, the study aligns consumer centric data sovereignty with Sustainable Development Goals SDG 9, SDG 12, and SDG 16 by supporting resilient digital infrastructure, responsible data usage, and transparent governance mechanisms. The findings offer implications for policymakers, platform designers, and organizations seeking privacy oriented digital governance models grounded in consumer empowerment.